The Wage System (Ijarah) In Islam: A Comparative Perspective of the Scholars - Ahmad Fauzi (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2021)
Wages are one of the main sources of income for workers for what they do to improve their lives. The wages given by the owner of the field must be in accordance with the principles of justice or not indicated to be wrongful. This study aims to determine the perspective of the scholars on the wage system (ijarah). This study was qualitative, the data collection technique in this study used documentation techniques by conducting in-depth studies related to the concept wage system in Islamic perspective contained in the works of Muslim intellectuals in the past and contemporary era. The data analysis technique used qualitative data analysis. The results found that the wage system applied by the current employer is in accordance with the concept of ijarah bil-amal contract because it has fulfilled all the pillars and requirements as well as the principles specified in the concept of this contract.